2009
DOI: 10.1016/j.jada.2008.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Three Popular Diets on Lipids, Endothelial Function, and C-Reactive Protein during Weight Maintenance

Abstract: Although popular diets focus on weight loss and their favorable biochemical and physiological effects, fewer investigations have evaluated the biological impact of these diets during weight maintenance. To study this issue, three popular diets, Atkins, South Beach and Ornish were tested in a randomized and counterbalanced, crossover study between January and December 2006. Participants completed each of the three 4-week isocaloric dietary intervention phases followed by a 4-week washout period. They were weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 13 publications
3
40
0
Order By: Relevance
“…Among those 773 participants, 548 (71%) completed this 6-mo weight-maintenance intervention. The dropout rates (18% for the LCD and 29% for weight maintenance) have been discussed in detail previously (18) and are in line with reports from other dietary studies (20)(21)(22). CID, clinical investigation day; DiOGENES, Diet, Obesity and Genes; LCD, low-calorie diet; QC, quality control; RT-qPCR, reverse transcription quantitative polymerase chain reaction; RNAseq, RNA sequencing.…”
Section: Methodssupporting
confidence: 78%
“…Among those 773 participants, 548 (71%) completed this 6-mo weight-maintenance intervention. The dropout rates (18% for the LCD and 29% for weight maintenance) have been discussed in detail previously (18) and are in line with reports from other dietary studies (20)(21)(22). CID, clinical investigation day; DiOGENES, Diet, Obesity and Genes; LCD, low-calorie diet; QC, quality control; RT-qPCR, reverse transcription quantitative polymerase chain reaction; RNAseq, RNA sequencing.…”
Section: Methodssupporting
confidence: 78%
“…In addition to blood pressure, we examined vascular health using two other non-invasive techniques, namely FMD and FBF. Prior work has shown variable effects of a CRD on VEF [25][26][27]. In our previous work we demonstrated that consumption of a CRD for 12 weeks, compared with a low-fat diet, improved FMD assessed postprandially following a high-fat meal [6].…”
Section: Discussionmentioning
confidence: 73%
“…24 -28 However, little is known about the effects of subsequent non-energy-restricted diets varying in protein content and glycemic index on these end points. Previous studies comparing different diets under ad libitum conditions were small and of short duration 29,30 or included patients with other comorbidities such as diabetes mellitus. 8 Moreover, the design of the DiOGenes study allowed a clear separation of the effects of caloric restriction from those of dietary composition.…”
Section: Discussionmentioning
confidence: 99%